A novel once-data-exchange method for solving transmission and distribution networks coordinated ACOPF model. (December 2020) - Zhang, Di; Miao, Shihong; Li, Chao; Zheng, Zhong; Yang, Weichen; Han, Ji; Li, Yaowang
Highlights: A function of the optimal goal to the active power injection is proposed. A function of the reactive power injection to the active power injection is proposed. A new method for the coupled ACOPF of transmission-distribution networks is designed. Abstract: With the scale increase of distributed generation, the coupling feature between the transmission and distribution networks is further enhanced. The separate optimization mechanisms of the networks cannot adapt to the development of the situation, which would bring some problems to power system operation. Thus, it has become an urgent task for the power system to solve the coordinated Alternating Current Optimal Power Flow (ACOPF) model for the transmission and distribution networks. However, the performance of the traditional centralized method is unsatisfactory in solving such large scale optimization problems for the high computing requirements. In this paper, a novel once-data-exchange method is developed to solve the coordinated ACOPF model. Firstly, the relationship between the optimal objective function and the active power demand at the boundary in the distribution network is described by a piecewise linear continuous function. Secondly, the reactive power demand at the boundary of the distribution network is converted to a piecewise linear continuous function of the active power demand at the boundary. Based on the two functions, the coordinated ACOPF model could be easily simplified to a mixed-integer programming problem. Numerical test results indicate that the proposed method performs better than the traditional methods in accuracy and computational efficiency.